(3LhGeY CfhGQ GdoefJbi hGdGSJPcGQs - (3CHhYHO Gddg eMeO Hf SYjO Hf CMeO GdCfUGQj GdeYQha HGHf RQbhfs; (3eGdc Hf CfS Hf eGdc GdCUHMj GdMejQj, CHh YHO Gddg,J (B179 (3g` s
(3ChdgG (B:s
(3jHJOF ef cJGH GdNdY s
(3BNQgG (B:s
(3hjfJgi HcJGH GdbVGA s
(3GdfSNI HgG MhGTs
(3hgh TQM Ydi ehWC GdEeGe eGdcs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
Keywords: (3GdMOjK h GdeUWdMs